2013
DOI: 10.1016/j.bbi.2013.01.087
|View full text |Cite
|
Sign up to set email alerts
|

Expression of immune genes on chromosome 6p21.3–22.1 in schizophrenia

Abstract: Schizophrenia is a common mental illness with a large genetic component. Three genome-wide association studies have implicated the major histocompatibility complex gene region on chromosome 6p21.3-22.1 in schizophrenia. In addition, nicotine, which is commonly abused in schizophrenia, affects the expression of central nervous system immune genes. Messenger RNA levels for genes in the 6p21.3-22.1 region were measured in human postmortem hippocampus of 89 subjects. The effects of schizophrenia diagnosis, smoking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 54 publications
1
23
0
2
Order By: Relevance
“…Furthermore, both HLA-A and ZNRD1 contain SNPs associated with schizophrenia by GWAS; rs2524005 is intronic in HLA-A (Bergen et al, 2012) and rs8321 is in the 3 0 untranslated region of ZNRD1 (Cross-Disorder Group of the Psychiatric Genomics Consortium, 2013b). In addition, HLA-A expression has shown evidence for alteration in schizophrenic patients (Sinkus et al, 2013). The most significantly associated SNP outside the HLA locus, in another recent GWAS study, is linked to a locus affecting HLA-A mRNA level in brain (Schizophrenia Working Group of the Psychiatric Genomics, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, both HLA-A and ZNRD1 contain SNPs associated with schizophrenia by GWAS; rs2524005 is intronic in HLA-A (Bergen et al, 2012) and rs8321 is in the 3 0 untranslated region of ZNRD1 (Cross-Disorder Group of the Psychiatric Genomics Consortium, 2013b). In addition, HLA-A expression has shown evidence for alteration in schizophrenic patients (Sinkus et al, 2013). The most significantly associated SNP outside the HLA locus, in another recent GWAS study, is linked to a locus affecting HLA-A mRNA level in brain (Schizophrenia Working Group of the Psychiatric Genomics, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…HLA class I proteins present peptides to cytotoxic T-cells (CD8+), while HLA class II proteins present peptides to helper T-cells (CD4+) participating in the production of antibodies by B-cells (Shiina et al, 2009;Trowsdale and Knight, 2013). The expression of cytokines and genes of the HLA region, critical components of the immune response, may be altered in peripheral immune cells and in glial cells of schizophrenic patients (Bernstein et al, 2015;Goudriaan et al, 2014;Miller et al, 2011;Sinkus et al, 2013). Several studies have shown a co-segregation of autoimmune diseases, chronic inflammation and maternal infection with schizophrenia (Bergink et al, 2014;Bernstein et al, 2015;Horvath and Mirnics, 2014;Knuesel et al, 2014;Stringer et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly polymorphisms of the IL1B gene have been linked to decreased prefrontal metabolic rates as determined using PET imaging (Papiol et al, 2007). Genome-wide association studies (GWAS) have also implicated tissue growth factor beta (TGF-beta) and tumour necrosis factor receptor 1 (TNFR1) signalling changes (Jia et al, 2010) and the major histocompatability complex (MHC) (Purcell et al, 2009;Stefansson et al, 2009) region on chromosome 6p21.3 to 6p22.1 in schizophrenia and post-mortem transcriptomic studies have shown that brains from schizophrenia patients have significant alterations in mRNA transcripts arising from genes in the MHC region (Kano and Altered, 2011;Sinkus et al, 2013). Considering this evidence, it is interesting to note that activation of the peripheral immune system over a prolonged duration causes activation of the brain's immune system and this has been linked to the onset of depressive episodes (Dantzer et al, 2008).…”
Section: Inflammation and Oxidative Stress Pathwaysmentioning
confidence: 99%
“…That assumption was disproved about 15 years ago when the Shatz laboratory made the surprising discovery that MHCI molecules are expressed in the CNS throughout development (41). mRNA encoding MHCI is expressed in neurons and glia from multiple brain regions in many species including mice, rats, cats, marmosets, and humans (1921, 4145). MHCI protein levels in the rodent cerebral cortex are highest during neonatal development and decrease to lower levels late in development and into adulthood (45, 46), followed by an increase again with aging, at least in glial cells (47).…”
Section: Mhci In the Cnsmentioning
confidence: 99%
“…Inflammation in the CNS is present in postmortem brains and cytokine levels are altered in the blood, brain, and cerebrospinal fluid (CSF) in SZ (4, 16, 17); specific cytokines may be correlated with periods of active psychosis (18). The expression of many immune-related genes in the brain, including MHC genes, is also altered in SZ (Horvath and Mirnics review, this issue) (1921). Reports showing a relationship between SZ endophenotypes and MHC class I (MHCI) expression support this association (8).…”
mentioning
confidence: 99%